Indoor microbial contamination and its relation to physical indoor air quality characteristics at selected libraries in pahang - A, Hizzri; H, Khadijah; Nordin, Noor Faizul Hadry; A., Norhidayah; Mohd. Aris, Mohd Shukri (Universiti Teknologi Malaysia, 2015)
Library contains huge collection of books that can undergo biodeterioration process after period of time. Due to this biological reaction, the existence of airborne particulate matters and microbes in the air of the library can be disturbed and elevated, thus can cause health implications to occupants. Therefore, it is an urge to assess and understand the correlation between physical indoor air quality (IAQ) characteristics, airborne pollutants and microbial contaminants in different library settings and locations. This study was carried out at three different libraries, which are Library A (Gambang as suburban area), Library B (Kuantan as urban area) and Library C (Pekan as rural area). The physical IAQ characteristics and particulate matter (PM) monitoring were assessed by using IAQ Meter and DustMate respectively. Surface Air System IAQ (SAS IAQ) was used to collect the airborne microbes. The microbial contamination was further assessed and identified in the laboratory by using API 20E and API 20 Strep while SPSS was used to analyze the relationship of physical IAQ characteristics, airborne pollutants and airborne microbes contaminants. The scientific method protocol and standard reference limits were compared based on Industrial Code of Practise on Indoor Air Quality, 2010 (ICOP, 2010) regulated by the Department of Occupational Safety and Health (DOSH). Respirable PM in Library A and CFU counts in Library A and C exceeded the standard limit with the value of 0.30 mg/m3, 2744 CFU/m3 and 1833 CFU/m3 respectively. Significant differences (p <0.05) between the selected libraries were observed among relative humidity (p=0.001), inhalable PM (p=0.001), thoracic PM (p=0.001), respirable PM (p=0.01), CO2 reading (p=0.001) and CFU counts (p=0.01). This study demonstrated Library C has poor air quality as the reading for CO2 and CFU counts are very high compared with the other two libraries. The bacterial identification findings indicated that Gram positive bacteria were abundant compared to Gram negative bacteria. Aerococcus viridans is the most dominant type of bacteria isolated in all the libraries.